„Wychowanie dobre dziecięciu szlacheckiemu” – Hieronim Baliński o edukacji - Żołądź-Strzelczyk, Dorota (Biuletyn Historii Wychowania, 2018)
Hieronim Baliński’s treatise on upbringing a noble boy, written in 1598, commissioned by Jan Łączyński for his son Kasper, has been used in literature for a long time. It is among the best known educational instructions the Old Polish period. Providing his guidance, Baliński showed exemplary education of a nobility boy. Baliński divided it into stages, taking into account the most important elements: religious and moral, physical and mental education. He also showed how to deal with a child and not discourage him from learning. In his opinion, religious education was of greatest importance as it was necessary for a young child to know God, His goodness, patience, mercy and love of human beings. The first stage of education was home schooling after which Baliński recommended a country school, followed by a trip abroad. A boy should take his first trip to Germany at the age of 12 and stay abroad for 2–3 years. According to Baliński, it was a prelude to the main journey which was to take place after a short stay at home. During the break, a young nobleman should be acquainted with the local law, operations of the court and the Parliament. Around the age of fifteen, a young man with a guardian appointed by his father should go abroad once again, this time to Italy, to develop his education and skills. Upon return from the trip, the young man continued education by transition to the adult life. Baliński recommended a court chancellery and military service. In the treatise he points out how a boy should behave towards other people; he also raised issues related to child nutrition and clothing. What is more, Baliński provided tips on physical development and exercises appropriate for children. The major source of Baliński’s treatise was religious literature although he probably referred to Quintilian’s and Mikołaj Rej’s works. According to his own account, Baliński drew on his experience and numerous conversations. The ideal man, as presented by him, bears resemblance to Rej’s faithful and mediocre “kind-hearted man”.